Bacterial cellulose membrane combined with BMSCs promotes wound healing by activating the notch signaling pathway - Wang, Xiaoyang; Zhao, Jie; Wang, Xiaochuan; Zhang, Jingjuan; Wang, Yi; Wang, Xinyue; Jia, Shanshan; Shi, Nian; Lu, Meiqi; Su, Hongxia; Zhang, Jixun; Jiang, Duyin (Frontiers in Surgery, 2023)
Objective: Bacterial cellulose membrane (BCM) has been widely studied and applied as a new biomaterial for wound healing but bring pain to patients with frequent dressing change. Local application of bone marrow mesenchymal stem cells (BMSCs) requires niche. Furthermore, the effect and mechanism of BCM combined with BMSCs have not been reported. Methods: Morphological and chemical identification of BCMs were investigated by porosity analyzer, SEM and FT-IR. Biological wound dressings (BWDs) were prepared by BCM in combination with BMSCs. The biological effects of BWDs on human dermal fibroblast (HDF) and VEGF-A in human vascular endothelial cell (HuVEC) were detected in vitro, the effect of BWDs on acute wounds in mice was detected in vivo. Collagen and angiogenesis were evaluated through HE and Masson staining. The expression of COL-1 and VEGF-A and the activation of Notch signaling pathway in vivo and in vitro were detected by qRT-PCR. Results: BCM was nanoscale in structure and provided a partial niche for the survival proliferation of BMSCs. BWDs were successfully prepared and regulated the biological behavior of wound healing-related cells in vitro, up-regulated the expression of COL-1 in HDF and VEGF-A in HuVEC. BWDs promoted wound healing by increasing collagen type I synthesis and angiogenesis in acute wounds in mice. Conclusions: BWDs prepared by the combination of nanomaterial BCMs and BMSCs facilitated acute wound healing, which may be regulated by activating the Notch signal pathway.